Implementation of a Hybrid Teleneuropsychology Method to Assess Middle Aged and Older Adults During the COVID-19 Pandemic. (6th June 2022) - Ceslis, Amelia; Mackenzie, Lisa; Robinson, Gail A
Abstract: Objective: Hybrid teleneuropsychology has emerged as a useful assessment method to manage physical distancing requirements during the COVID-19 pandemic. We describe the development of a hybrid teleneuropsychology clinic and compare results of six neuropsychological tasks across testing modalities, as well as a participant experience survey. Method: Healthy middle-aged and older adults completed a face-to-face assessment two years previously. Participants either completed reassessment face-to-face or via the hybrid setup. Results were compared across time points and delivery modality. Results: There were no significant differences in scores at reassessment between face-to-face and a hybrid setup on nonverbal fluid intelligence, verbal memory, visual memory, language, working memory or verbal initiation. Retest reliability was moderate to excellent for verbal and visual memory, attention and naming. Results of an anonymous survey indicated that participants felt comfortable and established good rapport with the examiner. Conclusions: This hybrid method of teleneuropsychology can be used to obtain high quality and reliable results including on tasks yet to be evaluated for teleneuropsychology, including the Graded Naming Test and the Topographical Recognition Memory Test.